Integrating Corporate Social Responsibility Awareness Into a Retail Management Course. (April 2018) - Beitelspacher, Lauren; Rodgers, Vikki L
Both students and industry are demanding that marketing instructors incorporate discussions of environmental and social responsibility into their courses. Marketing educators play a critical role in developing the knowledge and skills students need to effectively integrate corporate social responsibility (CSR) into their future business endeavors. Yet many educators struggle with developing meaningful and effective strategies to incorporate CSR authentically into their curricula. The project discussed in this article outlines a learning tool that encourages students to consider CSR in the context of their own purchase decisions while also considering CSR from a broader macro environmental perspective. The main goal is to build a CSR awareness that extends beyond a student's initial purchase exchange. Using retail as the context, students are required to consider CSR challenges including labor laws, environmental regulations, sourcing issues, and so on from the retailer and supplier relationships as well as the retailer and consumer relationships. Based on preliminary results, students' awareness of CSR challenges throughout the supply chain increased and the project proved to be an effective way to engage students in real learning about CSR.